2018
DOI: 10.1111/gcb.14055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiple stressors on juvenile fish in estuaries of the northeast Pacific

Abstract: A key step in identifying global change impacts on species and ecosystems is to quantify effects of multiple stressors. To date, the science of global change has been dominated by regional field studies, experimental manipulation, meta-analyses, conceptual models, reviews, and studies focusing on a single stressor or species over broad spatial and temporal scales. Here, we provide one of the first studies for coastal systems examining multiple stressor effects across broad scales, focused on the nursery functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 75 publications
(141 reference statements)
0
16
0
Order By: Relevance
“…We relied on the authors of the original publications to supply information on such variables, but unfortunately these were not consistently reported enough to support rigorous analysis (see Supporting Information). A recent meta‐analysis also suggested that abiotic conditions can greatly influence the nursery function of coastal habitats (Igulu et al., ), and other reviews of nurseries along the Northeast Pacific (Hughes et al., ) and Northeast Atlantic coasts (Brown et al., ) found that numerous human‐induced stressors can pose a risk to the nursery function (Toft et al., ). To date, however, explicit examples of nursery impairment due to anthropogenic or other environmental factors are rare and should be considered as an important next step for nursery research.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on the authors of the original publications to supply information on such variables, but unfortunately these were not consistently reported enough to support rigorous analysis (see Supporting Information). A recent meta‐analysis also suggested that abiotic conditions can greatly influence the nursery function of coastal habitats (Igulu et al., ), and other reviews of nurseries along the Northeast Pacific (Hughes et al., ) and Northeast Atlantic coasts (Brown et al., ) found that numerous human‐induced stressors can pose a risk to the nursery function (Toft et al., ). To date, however, explicit examples of nursery impairment due to anthropogenic or other environmental factors are rare and should be considered as an important next step for nursery research.…”
Section: Discussionmentioning
confidence: 99%
“…However, this highlights the importance of efforts to understand causal mechanisms for conservation biology (Hof et al, 2011). Studies on multiple stressors have mostly focussed on abundance or presence/absence data (e.g., Toft et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is now a substantial body of work on the biological impacts of changing estuaries (e.g. Cloern et al, ; Toft, Cordell, Simenstad, & Stamatiou, ). To make informed decisions on the management of a variety of estuary types, from those that have been impacted for hundreds to thousands of years, to those that may be closer to ‘pristine’, there is a need to synthesize the body of knowledge.…”
Section: Introductionmentioning
confidence: 99%